2010
DOI: 10.1002/stem.295
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Promotes Efficient Differentiation of Human Embryonic Stem Cells to Functional Endothelium

Abstract: Early development of mammalian embryos occurs in an environment of relative hypoxia. Nevertheless, human embryonic stem cells (hESC), which are derived from the inner cell mass of blastocyst, are routinely cultured under the same atmospheric conditions (21% O 2 ) as somatic cells. We hypothesized that O 2 levels modulate gene expression and differentiation potential of hESC, and thus, we performed gene profiling of hESC maintained under normoxic or hypoxic (1% or 5% O 2 ) conditions. Our analysis revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 58 publications
3
88
0
Order By: Relevance
“…These findings were in accordance with the hypothesis that stem cells with long-term engraftment capabilities were predominantly located at the lowest end of an oxygen gradient in the bone marrow, in hypoxic regions containing sinusoids rather than capillary structures [21]. Other studies have shown that stem cells were resistant to hypoxia-induced apoptosis [14], and hypoxia induced the production and secretion of factors that stimulate inflammation and neovascularization [22,23]. The present study confirmed the hypoxia-resistance of MSCs and showed the partial preservation of their innate properties in hypoxic versus normoxic cells.…”
Section: Discussionsupporting
confidence: 89%
“…These findings were in accordance with the hypothesis that stem cells with long-term engraftment capabilities were predominantly located at the lowest end of an oxygen gradient in the bone marrow, in hypoxic regions containing sinusoids rather than capillary structures [21]. Other studies have shown that stem cells were resistant to hypoxia-induced apoptosis [14], and hypoxia induced the production and secretion of factors that stimulate inflammation and neovascularization [22,23]. The present study confirmed the hypoxia-resistance of MSCs and showed the partial preservation of their innate properties in hypoxic versus normoxic cells.…”
Section: Discussionsupporting
confidence: 89%
“…A previously mentioned study found that an increase in ROS, which would lead to an increase in oxidized metabolites, led to cardiac differentiation (Serena et al, 2009) and mesodermal/ endodermal differentiation (Ji et al, 2010). Oxygen tension may also affect differentiation (Chen et al, 2010b;Lim et al, 2011) as, similar to hESC culture, differentiation protocols do no tend to use physiological levels of oxygen, as is shown in the production of retinal progenitor cells (Bae et al, 2011), mesoderm and cardiac cells (Niebruegge et al, 2009), chondrocytes (Koay andAthanasiou, 2008) and functional endothelium (Prado-Lopez et al, 2010) from hESCs. Multiple studies have also been undertaken in self-renewing and differentiating hESCs/hiPSCs to identify differentially expressed proteins, which may then become targets for small moleculemediated modulation (Chaerkady et al, 2011;Gerwe et al, 2011;Novak et al, 2011;Kim et al, 2011c).…”
Section: Metabolomicsmentioning
confidence: 99%
“…Previous studies have shown that hypoxic conditions are beneficial to stem and progenitor cell growth and survival because the embryonic environment in which these cells are often found are typically under low oxygen tension (2,8). Additionally, the self-degradation of damaged intracellular components, or autophagy, has been shown to have a "protective" effect during times of cellular stress (7).…”
Section: Number Of Viable Epcsmentioning
confidence: 99%